Effect of fluid and driving pressure on cyclical “on–off” flow of pulmonary microcirculation during mechanical ventilation - Siyi Yuan; Xiangyu Chen; Liangyu Mi; Yi Chi; Haoping Huang; Bo Liu; Chaofu Yue; Zeming Zhao; Longxiang Su; Yun Long; Şakir Akin; Can Ince; et al. (Intensive Care Medicine Experimental)
Abstract Objectives This study aimed to identify the cyclical “on–off” flow of pulmonary microcirculation during inspiration and expiration by sidestream dark field imaging (SDF) technology in vivo and investigate the effects of volume status and driving pressure on cyclical “on–off” flow of microcirculation. Methods 24 ARDS-modeled rabbits were randomly divided into high-driving pressure group (HDP group) and low-driving pressure group (LDP group). Lung microcirculation measurements were performed using the SDF microscope at two timepoints (T1 CVP 2–4 mmHg, T2 CVP 8–10 mmHg). From T1 to T2, 10 ml/kg saline was infused to increase CVP. The cyclical “on–off” pulmonary microcirculation was quantitatively assessed by the change of microcirculation between expiration and inspiration. Results Proportion of perfused vessels (PPV), microvascular flow index (MFI), perfused vessel density (PVD), and total vessel density (TVD) at expiration were significantly higher than inspiration in the HDP group. The HDP group has a higher ΔPPV and ΔPVD. After fluid loading, ΔPPV and ΔMFI decreased. TNF-α, IL-6, Ang-2, and vWF levels in the HDP group were higher. The HDP group also has a higher lung wet-weight/body weight ratio, lung wet-to-dry weight ratio, and more severe damage of pulmonary capillaries than the LDP group. Conclusions The difference in alveolar perfused microcirculation between inspiration and expiration defined as cyclical “on–off flow” can be detected. High driving pressure can enhance the cyclical “on–off” flow, and fluid loading can relieve it. High driving pressure can potentially cause injury to pulmonary capillaries due to the phenomenon of “on–off” flow, thereby exacerbating ARDS.